Semi-analytical dynamic modeling and impact mechanism analysis of a hard-coating cylindrical shell with arbitrary circular perforations - Jian Yang; Yue Zhang (Scientific Reports)
Abstract In this paper, an innovative axial domain decomposition method, which uniquely integrates axial and circumferential perforation parameters, is developed for semi-analytical modeling of free vibration of a hard-coating cylindrical shell with arbitrary axial and circumferential perforations, based on the Love’s first-order shear deformation theory and Rayleigh-Ritz method. The concept of this method is to decompose the shell into two types of domains at the upper and lower axial boundaries of the circular perforations. The generalized semi-analytical formulas of the perforated composite shell can be derived by assembling the separated energy expressions of each domain. Moreover, the result analysis find that the intrinsic influence mechanism of the circumferential perforation number on vibration characteristics, that is, a precipitous alteration in the natural frequency occurs only when the ratio of the circumferential perforation number to the circumferential wave number equals to one divided by an odd number as well as two divided by an even·number. The special phenomenon can provide an important theory support for the vibration reduction design of the perforated hard-coating cylindrical shells in the aerospace engine.